Analisis Manajemen Risiko Lingkungan, Sosial dan Tata Kelola pada Usaha Budidaya dan Pengolahan Kelapa Sawit (Studi Kasus: PT PP London Sumatra Tbk) - Meilan, Tria Mutiari; Raharja, Sapta; Syamsun, Muhammad (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
Palm oil (Elaeis guineensis Jacq.) is one of the main commodities in Indonesia . The production of Crude Palm Oil (CPO) and Palm Kernel Oil (PKO) in Indonesia has increased significantly in recent years. The palm oil industry is often accused of causing environmental degradation because some of the cultivation and processing practices are suspected to cause greenhouse gas emissions. The Government has implemented the obligations of certification of Indonesia Sustainable Palm Oil (ISPO) in accordance with the Government of Indonesia's commitment to improve the sustainability of the Indonesian palm oil industry. The objectives of this research are (1) To identify and analyze the impact of risk on environment, social and governance (ESG Risk) at each stage of oil palm cultivation and processing. (2) To identify and analyze the level of readiness to fulfill ISPO requirements (3). Determine the recommendations of risk control in the cultivation and processing of oil palm. The method used in this research is descriptive and analytic method which is a case study. Results of analysis at PT. London Sumatra (Lonsum) especially at Arta Kencana Estate, Lahat, South Sumatera which was not ISPO Certified yet, shows that there are 16 ESG risks and the highest is related to the preparation stage of the land area.  Risk control recommended is Risk Avoidance. Arta Kencana Estate in general have fulfilled almost all of the requirements for compliance with required principles with an average index of 8.86.  Arta Kencana Estate are need to complete and perform administrative improvements and requirements documents to be able to meet the gap. In this study found that the ESG risk on palm oil can be mitigated through the fulfillment of ISPO principles.